VACCINE HESITANCY IN COLLEGE STUDENTS - GilbertEsparza, Emily (My University, 2021)
Vaccine hesitancy is a growing public health concern in the United States, especially in the wake of the COVID-19 pandemic. The World Health Organization (WHO) lists vaccine hesitancy on its “10 Threats to Global Health in 2019” and defines it as “a delay in acceptance of or refusal of vaccines despite the availability of vaccine services”. Studies have shown that young adults are less likely to get vaccinated against COVID-19. A portion of my public health practice consisted of investigating vaccine hesitancy in college students on Kansas State University campus during summer 2021 by administering an anonymous survey related to vaccination behaviors and opinions. Another portion of my public health practice consisted of spending time at Lafene Health Center and visiting with staff members of various departments. My main objective was to learn Lafene’s COVID-19 procedures from the time a patient walks in the door up until they are released from quarantine/contact tracing. I created an infographic for student outreach about how to help keep yourself and others safe from COVID-19. I also worked with Riley County Health Department (RCHD) to help provide COVID-19 testing and vaccine clinics to the residents of Riley County at no charge. I had several duties including helping individuals administer self-tests, filling out vaccine cards, and disseminating COVID-19 vaccine information/tips. I also created two infographics for RCHD outreach materials related to frequently asked vaccine questions and COVID-19 vaccine-specific facts.
Keywords: public health; vaccine hesitancy; Covid-19; college students; global health